2012
DOI: 10.1007/s00382-012-1331-2
|View full text |Cite
|
Sign up to set email alerts
|

Linear trends in sea surface temperature of the tropical Pacific Ocean and implications for the El Niño-Southern Oscillation

Abstract: A principal component decomposition of monthly sea surface temperature (SST) variability in the tropical Pacific Ocean demonstrates that nearly all of the linear trends during 1950-2010 are found in two leading patterns. The first SST pattern is strongly related to the canonical El Niño-Southern Oscillation (ENSO) pattern. The second pattern shares characteristics with the first pattern and its existence solely depends on the presence of linear trends across the tropical Pacific Ocean. The decomposition also u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 50 publications
3
60
0
Order By: Relevance
“…Finally, increased SST associated with climate change might have gradually modulated ENSO's behaviour [25][26][27] , predictability 4 and impacts on the yields. We also note that further assessment is needed for the impacts on yields because of other major climate modes such as the Indian Ocean Dipole 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, increased SST associated with climate change might have gradually modulated ENSO's behaviour [25][26][27] , predictability 4 and impacts on the yields. We also note that further assessment is needed for the impacts on yields because of other major climate modes such as the Indian Ocean Dipole 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…These distributions of ENSO classes are closely related to the long‐term trend of the CTM under global warming. In addition, although some studies suggested that the third EOF mode (EOF3) of the tropical Pacific SSTA can well represent the Modoki mode (e.g., L'Heureux et al, ), the EOF3 mode only accounts for 64% of the Modoki variance. It is also noted that the composite SSTA for the combinations of the EOF3 mode and ENSO (not shown) is different from the composite SSTA for the combinations of the CTM and ENSO (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…One might hypothesize that the zonal structure of the temperature trend is due to aliasing of an ENSO signal, as ENSO clearly impacts temperatures in the tropical lower stratosphere [ Kiladis et al , ; Calvo Fernández et al , ; Scherllin‐Pirscher et al , ; Garfinkel et al , ]. Scaife et al [] further argue that El Niño frequency has increased (a more recent discussion of changes in Pacific Ocean SSTs and ENSO frequency can be found in L'Heureux et al [], Luo et al [], and Sohn et al []), and thus SST changes may have led to warmer cold‐point temperatures. The present study suggests that trends in ENSO frequency have not caused the trends in the cold‐point temperatures.…”
Section: Discussionmentioning
confidence: 99%